BUSINESS MODEL APPLICATION IN HIGHER EDUCATION INSTITUTIONS: A STRUCTURED REVIEW - Sharmili Mohamed Rafi; Engku Mohamad Engku Abdullah (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
The application of business models within higher education institutions (HEIs) has gained considerable attention to enhance strategic management and sustainability. This structured review examines the current landscape of business model integration in HEIs, focusing on its impact on sustainability, innovation, and institutional performance. The study addresses the growing concern that while the strategic importance of sustainability is widely acknowledged, the practical implementation of business models within universities remains underexplored. A systematic review methodology was employed, analyzing recent literature from academic databases to identify key themes and trends in applying business models in higher education. The findings were divided into three themes: (1) Sustainable Management and Innovation in Higher Education, (2) Digital Transformation and Quality in Higher Education, and (3) Entrepreneurship and Social Impact in Education. The findings reveal various approaches and varying degrees of success influenced by institutional size, geographical location, and existing strategic orientations. Notably, the review highlights the importance of aligning business models with sustainability goals, emphasizing the need for frameworks that integrate sustainability into the core operations of HEIs. Additionally, the study underscores the role of innovation ecosystems in fostering entrepreneurial activities and adapting to external challenges. The review concludes that while business models are increasingly being recognized as vital tools for enhancing institutional sustainability and innovation, there is a significant need for further research to develop practical frameworks that can be effectively implemented across diverse educational contexts.